Cognitive Human-Machine Interface Applied in Remote Support for Industrial Robot Systems. (4th October 2013) - Kosicki, Tomasz; Thomessen, Trygve
An attempt is currently being made to widely introduce industrial robots to Small-Medium Enterprises (SMEs). Since the enterprises usually employ too small number of robot units to afford specialized departments for robot maintenance, they must be provided with inexpensive and immediate support remotely. This paper evaluates whether the support can be provided by means of Cognitive Info-communication – communication in which human cognitive capabilities are extended irrespectively of geographical distances. The evaluations are given with an aid of experimental system that consists of local and remote rooms, which are physically separated – a six-degree-of-freedom NACHI SH133-03 industrial robot is situated in the local room, while the operator, who supervises the robot by means of audio-visual Cognitive Human-Machine Interface, is situated in the remote room. The results of simple experiments show that Cognitive Info-communication is not only efficient mean to provide the support remotely, but is probably also a powerful tool to enhance interaction with any data-rich environment that require good conceptual understanding of system's state and careful attention management. Furthermore, the paper discusses data presentation and reduction methods for data-rich environments, as well as introduces the concepts of Naturally Acquired Data and Cognitive Human-Machine Interfaces.